Pengembangan Modul Pembelajaran Kontekstual disertai Concept Mapping pada Materi Elastisitas dan Hukum Hooke - Fartina Fartina; Laxmi Zahara; Khaerus Syahidi; Hikmatul Qudsiah (Kappa Journal, 2021)
This research aims to develop and determine the quality of the contextual learning module accompanied by a concept mapping  of elasticity material andlaw Hooke  in class XI IPA MA Mu'allimat NW Pancor students. This type of research is research and development. The method used in this research is 4-D method, which consists of the stages of define, design, development and dissemination. This research is limited to the stage, development namely the development test on a limited scale. The data in this study were analyzed descriptively qualitatively. The research subjects included 3 lecturers and 3 physics teachers as validators, and students of class XI IPA 1 MA Mu'allimat NW Pancor as respondents. The validation of lecturers and physics teachers both resulted in a score of 3.85 and the development trial on a limited scale resulted in a score of 3.88. All research results indicate that the module is feasible to be developed.